More Than Suppression: Glucocorticoid Action on Monocytes and Macrophages - Ehrchen, Jan M.; Roth, Johannes; Barczyk-Kahlert, Katarzyna (Frontiers in Immunology, 2019)
Uncontrolled inflammation is a leading cause of many clinically relevant diseases. Current therapeutic strategies focus mainly on immunosuppression rather than on mechanisms of inflammatory resolution. Glucocorticoids (GCs) are still the most widely used anti-inflammatory drugs. GCs affect most immune cells but there is growing evidence for cell type specific mechanisms. Different subtypes of monocytes and macrophages play a pivotal role both in generation as well as resolution of inflammation. Activation of these cells by microbial products or endogenous danger signals results in production of pro-inflammatory mediators and initiation of an inflammatory response. GCs efficiently inhibit these processes by down-regulating pro-inflammatory mediators from macrophages and monocytes. On the other hand, GCs act on “naïve” monocytes and macrophages and induce anti-inflammatory mediators and differentiation of anti-inflammatory phenotypes. GC-induced anti-inflammatory monocytes have an increased ability to migrate towards inflammatory stimuli. They remove endo- and exogenous danger signals by an increased phagocytic capacity, produce anti-inflammatory mediators and limit T-cell activation. Thus GCs limit amplification of inflammation by repressing pro-inflammatory macrophage activation and additionally induce anti-inflammatory monocyte and macrophage populations actively promoting resolution of inflammation. Further investigation of these mechanisms should lead to the development of novel therapeutic strategies to modulate undesirable inflammation with fewer side effects via induction of inflammatory resolution rather than non-specific immunosuppression.